Transforming Junior High Student Elections: The Impact of Pancasila Student Profile Projects on School Democracy - Nindya Aulia Azzahra; Firman Umar; Najamuddin Najamuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Conventional student council elections often function as mere formalities, failing to serve as practical laboratories for democratic engagement and character development. This study evaluates the transformation of student elections through the Pancasila Student Profile Strengthening Project (P5) at Junior High School 1 Polongbangkeng Utara. The research focuses on three key dimensions: student participation levels, the implementation of democratic principles, and the development of civic skills among candidates. Employing a descriptive qualitative methodology, the study engaged teachers, students, and candidate pairs as primary informants. Data were gathered through interviews, systematic observation, and documentation, followed by analysis using data condensation, visualization, and conclusion drawing. Data validity was established via source triangulation. The findings demonstrate that: student participation reached an